Metabolic Benefit of Bulls Being Fed Moringa Leaves Twigs and Branches as a Major Concentrate Ingredient - Sultana, Nasrin; Das, Nani Gopal; Kabir, Md Ahsanul; Deb, Gautam Kumar; Islam, Md Tarequl (Frontiers in Animal Science, 2021)
The study was conducted to investigate nutrient metabolism and semen quality of bulls fed with moringa (Moringa oleifera) leaves, twigs, and branches as a major concentrate ingredient. Twenty-one Red Chittagong bulls of about 204 (±50) kg initial live weight (LW) were randomly divided into three equal LW groups. They were fed maize silage as a basal feedstuff for 65 days with the supplementation of concentrate mixtures at 1% of LW, consisting of either 0, 25, or 50% moringa mash on a fresh basis. Moringa mash was a sun-dried ground preparation of leaves, twigs, and branches of moringa. The results indicated that different levels of moringa in concentrate mixtures (0, 25, and 50%) did not change daily DM intake, digestibility, and LW gain of bulls (p > 0.05). However, increasing dietary moringa (up to 203 g/kg DM) significantly decreased production cost of methane (CH4) (methane emission [kg/kg gain] = 1.6422—[0.0059 × moringa intake, g/kg DM], n = 12, R2 = 0.384, P = 0.032) in a similar metabolizable energy intake level (0.21 ± 0.01 MJ/kg LW). Also, higher dietary moringa significantly reduced urinary nitrogen loss (urinary nitrogen [% digested nitrogen] = 43.0 – 0.069 × moringa intake [g/kg DM]; R2 = 0.3712, P = 0.034). Thus, increasing moringa by 1 g/kg DM decreased CH4 emission by 6 g/kg gain and absorbed nitrogen loss by 0.069 %. Also, progressive motility of sperm increased significantly (33.0, 51.0, and 60.1%, respectively; p = 0.03) in bulls fed with concentrate mixtures containing moringa at 0, 25, or 50%. It may be concluded that feeding moringa mash at 203 g/kg DM may decrease energy loss as methane and urinary nitrogen loss without impacting the production of beef cattle. Feeding moringa mash to beef cattle may abate dietary energy and nitrogen loss and consequently decrease the environmental pollution.